Wearable sensors based on artificial intelligence models for human activity recognition - Alarfaj, Mohammed; Al Madini, Azzam; Alsafran, Ahmed; Farag, Mohammed; Chtourou, Slim; Afifi, Ahmed; Ahmad, Ayaz; Al Rubayyi, Osama; Al Harbi, Ali; Al Thunaian, Mustafa (Frontiers in Artificial Intelligence, 2024)
Human motion detection technology holds significant potential in medicine, health care, and physical exercise. This study introduces a novel approach to human activity recognition (HAR) using convolutional neural networks (CNNs) designed for individual sensor types to enhance the accuracy and address the challenge of diverse data shapes from accelerometers, gyroscopes, and barometers. Specific CNN models are constructed for each sensor type, enabling them to capture the characteristics of their respective sensors. These adapted CNNs are designed to effectively process varying data shapes and sensor-specific characteristics to accurately classify a wide range of human activities. The late-fusion technique is employed to combine predictions from various models to obtain comprehensive estimates of human activity. The proposed CNN-based approach is compared to a standard support vector machine (SVM) classifier using the one-vs-rest methodology. The latefusion CNN model showed significantly improved performance, with validation and final test accuracies of 99.35% and 94.83% compared to the conventional SVM classifier at 87.07% and 83.10%, respectively. These findings provide strong evidence that combining multiple sensors and a barometer and utilizing an additional filter algorithm greatly improves the accuracy of identifying different human movement patterns.